Clinical Study Comparing Herbal Plant Extract as a Supportive Treatment for Chronic Periodontitis - Lagdive Sushma Sanjay; N. Shaikh Rukhshana; Madhad Vibhuti; Vasani Amit; Nikunj Prajapati; Dharmendra Shah; Miral Mehta; Dhaval Mehta (Journal of Pharmacy and Bioallied Sciences)
Introduction: To stop the processes that lead to the degradation of periodontal tissue, several host response modulation treatments and local medication therapies like use of ayurvedic and herbal medications have grown recently. Objectives: The purpose of this research was to evaluate the efficacy of curcumin gel as an adjunct to scaling and root planning (SRP) in the treatment of chronic periodontitis. Materials and Methods: 30 patients with chronic periodontitis were split into two groups at random in a split mouth research design. Only SRP was applied to control sites. After thorough scaling and root design, curcumin gel was placed intra pocket at the experimental areas. At 0, 1, and 3 months intervals, various clinical parameters were assessed in both groups. Results: All of the parameters in the test group were significantly reduced in comparison with the control group. Conclusion: Findings support application of curcumin gel to the management of periodontal diseases.